Fire tekststykker knyttet til samemisjonæren Thomas von Westen 1716-1723 - Randi Skjelmo (Sjuttonhundratal, 2017)
Four Texts Concerning Thomas von Westen's Mission among the Sámi 1716-1723. Thomas von Westen (1682-1727) was responsible for a mission concerning the Sámi population in Norway in the early Eighteenth-Century. The mission was initiated by the Danish-Norwegian King Frederik 4th and the Society for Promoting Lutheran Christianity in Copenhagen 1715. von Westen wrote a significant number of documents concerning the mission. These documents comprise instructions, reports, public correspondence, personal letters and statements. This article concerns four of these texts; a letter to the parish that von Westen worked in when he was appointed leader of missionary work (1716), a letter to the Society for Promoting Lutheran Christianity (1718), the Nærøy manuscript (1723) and finally a letter concerning the establishment of connections to ecclesiastical authorities in Swedish Lapland (1723). Thomas von Westen’s writings reflect his engagement in the mission, his preaching and how he introduced Christianity to the Sámi people by guiding them to personal consciousness and public confession. His documents reflect both his own ambitions and the public interest in the missionary work.